Environmental and Green Investment Regulations: The Impact of China's Belt and Green Road Initiative in Southeast Asia - Jing, Zhang; Zulyadi, Rizkan; Ramadhan, M. Citra (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
The Green Belt and Road Initiative (BRI), China's international development strategy, aims to improve regional connectivity while addressing the environmental challenges of major infrastructure projects. This study explores the impact of BRI on environmental regulations and green investment in Southeast Asia, given the importance of sustainable development in the global economy. Research methods include document analysis, project reports, academic literature, and interviews with stakeholders, as well as case studies. The results show that BRI is driving the transformation of environmental regulations in countries such as Viet Nam, Indonesia, and Thailand, and facilitating the shift towards green investment. Investments in renewable energy, sustainable urban planning, and green technology are growing. Despite challenges such as high costs and alignment of interests, BRI opens up opportunities for international cooperation and green market development. This research emphasizes the need for a multifaceted approach to balance economic growth and environmental protection.